Logistics Performance And Other Factors As Antecedents Of The Sustainability Performance Of G-20 Countries - Muhammad Ikhsan Harsono; wahyuningsih, wahyuningsih (International Journal of Economic Research and Financial Accounting, 2023)
Logistics directly affects the growth and development of a nation, making it a vital component of economic development (Hofman, 2017). Numerous studies have established a direct link between a country's economic progress and its logistics performance. This relationship encompasses various dimensions, including economic, developmental, environmental, and social aspects. Within the context of sustainable supply chain management, the environmental and social aspects are often highlighted (Seuring and Muller, 2008; World Bank, 2007, 2018; United Nations, 2010; OECD, 2011; World Economic Forum, 2015).The logistics industry has a significant impact on environmental and social issues and consumes a substantial amount of energy resources, leading to high carbon emissions (Rashidi and Cullinane, 2019). Thus, efforts to reduce carbon emissions are crucial. Initiatives such as developing adequate infrastructure like highways to reduce travel time and waiting times at ports for container unloading are essential. Elevating the competency and quality of logistics services also plays a role in improvement, as logistics professionals contribute not only to material movement but also support marketing functions, product development, pricing, and customer service. In Indonesia, a G-20 member, the logistics sector contributes significantly to the country's Gross Domestic Product (GDP). However, challenges related to infrastructure and environmental impact need to be addressed. In this regard, the Logistics Performance Index (LPI) published by the World Bank serves as a valuable tool to assess logistics performance and promote sustainability. Within the context of sustainability performance, this research aims to analyze the influence of Logistics Performance and other factors on sustainability performance in G-20 countries, with a focus on Indonesia. LPI data and other relevant indicators are employed to identify the effects of these variables on sustainability performance. The study is expected to offer insights for practitioners and organizations to take steps towards improved sustainability performance while also contributing theoretically to the field.